Symmetry in Engineering Sciences II - Montoya, Francisco G.; Baños Navarro, Raúl (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents a sample of theoretical and practical advances in symmetry in multidisciplinary engineering applications. It covers several applications, such as mechanical analysis of tunnel lining, prediction methods for the ring damper used in gears, calibration methods for manipulators, design methods for wheel configurations of mobile robots, analysis of elastic plastic damaged zones, 3D printed corneal models, analysis of multibody system dynamic networks, structural elements in architecture, railway transportation, transportation of hazardous materials, cable-driven mechanisms, and image processing. The contributions included in this book describe the state-of-the-art advances in this field and demonstrate the possibilities of the study of symmetry in multidisciplinary applications in the field of engineering.